Extração e exportação de nutrientes em cultivares de feijoeiro, sob níveis de adubação: II - Micronutrientes - Fernandes, Adalton Mazetti [UNESP]; Soratto, Rogério Peres [UNESP]; dos Santos, Letícia Andriani [UNESP] (FapUNIFESP (SciELO), 2013)
Where the level of agricultural technology is higher, common bean cultivars with a higher yield potential possibly require greater amounts of micronutrients. In Brazil however, there is a lack of information about the micronutrient extraction and exportation by the main grown cultivars. The objective of this study was to evaluate micronutrient (B, Cu, Fe, Mn, and Zn) extraction and exportation by common bean cultivars Pérola and IAC Alvorada, under different levels of NPK fertilization, on a dystroferric Red Nitosol, in Botucatu, São Paulo State, Brazil. The experiment was arranged in a randomized complete block (split plot) design with four replications. The plots consisted of six treatments based on a 2 x 3 factorial model, represented by two cultivars and three NPK levels (PD0 - 'Pérola' without fertilization, PD1 - 'Pérola' with 50 % of recommended fertilization, PD2 - 'Pérola' with 100 % of recommended fertilization, AD0 - 'IAC Alvorada' without fertilization, AD1 - 'IAC Alvorada' with 50 % of recommended fertilization, and AD2 - 'IAC Alvorada' with 100 % of recommended fertilization) and subplots sampled seven times during the cycle. Higher levels of NPK fertilization increased micronutrient extraction by both cultivars, and treatments with 100 % of recommended NPK fertilization extracted on average 167 g B, 58 g Cu, 1,405 g Fe, 1,213 g Mn and 211 g Zn per hectare. Regardless of the treatment, the highest demand period for B, Cu, Fe, Mn and Zn in both cultivars occurred at the R7 stage (pod formation), i.e. 42 to 55 days after emergence (DAE). The amount of B, Cu, Fe, Mn and Zn exported depended mainly on the level of NPK fertilization used, with values per hectare ranging from 38 to 90 g of B, 12 to 26 g of Cu, 222 to 568 g of Fe 234 to 467 g of Mn, and 40 to 96 g of Zn.
Nutrient extraction and exportation by common bean cultivars under different fertilization levels: II - Micronutrients
Keywords: Absorption curves; Absorption rates; Mineral nutrition; Nutrients accumulation; Phaseolus vulgaris